3가크롬 도금욕에서 펄스도금조건이 전류효율에 미치는 영향 - 황경진(Kyoung-Jin Hwang); 안종관(Jong-Gwan Ahn); 이만승(Man-Seung Lee); 오영주(Young-Joo Oh) (Biuletyn Uniejowski, 2003)
In order to investigate the effects of pulse plating conditions on the electrodeposition of trivalent chromium, electroplating experiments from bath with low concentration of trivalent chromium were performed. The variation of current efficiency of chromium electroplating with the electroplating conditions was explained. The maximum current efficiency of pulse plating is 6.4 times as high as that of direct plating at the same mean current density The nodular size increased with pulse plating time and the pulse frequency.